The Old Greek of Isaiah: issues and perspectives papers read at the Conference on the Septuagint of Isaiah, held in Leiden 10 - 11 April 2008 - Kooij, Arie van der 1945- (Leuven ; Paris ; Walpole, MA Peeters, 2010)
Literaturangaben
Bibliography of the Septuagint of Isaiah ; List of contributors ; Index of Hebrew words ; Index of Greek ; Index of ancient sources ; Index of modern authors.
Beitr. teilw. engl., teilw. franz
Beitr. teilw. engl., teilw. franz.
Archivierung/Langzeitarchivierung gewährleistet
Archivierung prüfen
Keywords: Bible -- Criticism, Textual -- Congresses; Bible -- Criticism, interpretation, etc -- Congresses; Bible -- Versions -- Septuagint -- Congresses; Konferenzschrift -- 2008 -- Leiden